DESIGN AND EVALUATION OF A WEB BASED VIRTUAL DSP LABORATORY USING GUI AND HTML (Journal of Engineering, 2011)
ABSTRACT:Engineering education should involve practical laboratory to support theoretical foundation and developstudent skills. These hands on laboratories have some disadvantages such as expensive, supervision required, time and place restrictions. This paper presents design and evaluation of a web based virtual laboratory for teaching Digital Signal Processing (DSP) to undergraduate students in Electromechanical Engineering Department at the University of Technology. The laboratory experiments includes classification of signals, sampling theorem, Fourier series, complex Fourier series, Fourier transform, inverse Fourier transform, discrete Fourier transform, Fast Fourier Transform (FFT),convolution , Z-transform, and digital filters. Graphical User Interface (GUI) feature of MATLAB have been used to provide students with a friendly and visual approach in specifying input parameters while Hyper Text Markup Language (HTML) was used to illustrate theoretical foundations. The questionnaire survey and five point Likert scale are utilized in performing evaluation. Results of this evaluation showed that the proposed virtual DSP laboratory was helped students in DSP concepts, made positive effects on students’ achievements and attitudes when compared to traditional teaching methods.